Gastrokinetic and Gastroprotective Activity of Gasex - Mohd. Azeemuddin Mukhram; Suryakant DA; Rafiq Mohamed; Patki PS, Rangesh S (International Journal of Phytomedicine, 2011)
Present study was aimed to evaluate the gastrokinetic and gastroprotective effect of Gasex a polyherbal formulation in experimental models of phenol red test meal method for gastrokinetic activity and acid-induced gastrointestinal lesions for gastroprotective activity. Gasex at a dose of 500 and 1000 mg/kg showed statistically significant gastrokinetic activity by increasing the percentage of gastric emptying and small intestinal transit, the higher dose of Gasex was comparable to the reference standard Domeperidone (10 mg/kg). The higher dose of Gasex (1000 mg/kg) showed gastroprotective activity by significantly decreasing the gastric volume and mean gastric lesion score and the same was reflected in histopathological findings. The present finding highlights few of the underlying modes of action of Gasex in the successful management of various gastrointestinal conditions.